Planning in India A Select Bibliography of Books, Articles and Official Publications - Planning Commission (Planning Commission, 1964)
Theory of Planning mid Economic Development Economics of Underdeveloped Countries Indian Economic Problem and Policies Planning In India and its Problems and Policies Socialistic Pattern of Society Plan upto 1950 First Five Year Plan Second Five Year Plan Third Five Year Plan Fourth Five Year Plan.
Government of India Planning Commission
Government of India Planning Commission